Financial innovations and economic growth: Does financial inclusion play a mediating role? - Daniel Domeher; Emmanuel Konadu-Yiadom; Godfred Aawaar (Cogent Business & Management, 2022)
Innovations in the financial sector play a critical role in promoting economic growth. Studies that have sought to investigate this linkage in sub-Saharan Africa have produced mixed results. None of the existing studies have attempted to examine the possible mediating role of financial inclusion in explaining the relationship between innovations and growth. This paper thus sought to establish if financial inclusion mediates the relationship between innovation and growth. Secondary data from (26 selected SSA countries over the period 2004 to 2017 were used. The data were analysed using the GMM estimation technique. It was found amongst other things that investments in innovations in the banking sector promote financial inclusion. In addition, financial inclusion fully mediates the relationship between innovation and economic growth. It is thus recommended that governments in the sub-region invest in the appropriate technological infrastructure that the banking sector can leverage on in the provision of banking services as the key to promoting financial inclusion and economic growth.
Keywords: 650; financial inclusion; economic growth; financial innovation; mediation analysis; Sub Saharan Africa